Strategi Mempertahankan Pemasaran Unit Layanan Gadai Syariah Sultan Adam Banjarmasin dalam Meningkatkan Penjualan Jasa Produk - Adib Mustanir; Zakky Zamrudi; Syahrial Shaddiq; S. Purnamasari (Jurnal Ekonomi Islam, 2025)
Human resources are a crucial asset for a company because they are responsible for making decisions and taking action in the company. Companies really want HR (Human Resources) who are talented, gifted, competent and classy. In implementing marketing strategies to maintain their business, creative and innovative power of workers or employees is needed in an institution, including at the Sultan Adam Banjarmasin Sharia Pawnshop Unit which always strives to ensure that the business being run can survive in the midst of competition like today with its strategies. The problem formulation in this study is how the marketing strategy of Pegadaian Sharia Service Unit Sultan Adam Banjarmasin in increasing sales of its product services. The purpose of this study is to analyze how the marketing strategy carried out by Pegadaian Sharia Service Unit Sultan Adam Banjarmasin in increasing sales of its product services so that it can survive. The research method used in this study is qualitative research with data collection techniques using observation, interviews, and documentation. The results of this study are the marketing strategy used based on three important factors as the basis of the marketing concept and at the same time as the basis of the marketing strategy in its marketing mix, namely: consumer orientation, coordination and integration within the company and gaining profits through consumer satisfaction.